Mpox global emergency: strengthening African leadership - Abubakar, Ibrahim; Lutwama, Julius; Kyobutungi, Catherine; Sankoh, Osman (Elsevier Ltd, 2024)
The resurgence of mpox during 2024 has been declared a continental emergency by the Africa Centres for Disease Control and Prevention (Africa CDC) and a Public Health Emergency of International Concern (PHEIC) by WHO and now affects 15 African countries.1,2 In Africa between Jan 1, 2024 and Sept 16, 2024, there were 6201 confirmed mpox cases and 32 confirmed deaths, among a much larger number of suspected cases and deaths.2 Cases of clade 1b mpox causing the current sustained human-to-human transmission are concentrated in Burundi, Central African Republic, Republic of the Congo, DR Congo, Kenya, Rwanda, and Uganda, while cases of clade 1a mpox have been reported from multiple countries across Central Africa associated with spillover events from animal reservoirs.2 Cases of clade 2 have been reported from Cote d'Ivoire, Liberia, Nigeria, and South Africa.2 The majority of cases and deaths have been reported in DR Congo, with an outsize toll on children.2 The epidemiology of mpox continues to evolve and gaps remain in our knowledge; evidence suggests there might be potential transmission from mother to fetus in utero and during breastfeeding.3,4 Further cases of clade 1 mpox have been reported beyond Africa including single cases in Sweden and Thailand.5 Calls for global action and response are important, especially for equity and solidarity in sharing countermeasures such as diagnostics and vaccines. Examples of African-led epidemiological research to understand transmission include the elucidation of the emergence of clade 1 with predominance of APOBEC3-type mutations associated with a propensity for human-to-human transmission11 and previous work on the clade 2b outbreak in Nigeria that helped identify the sexual spread of mpox.12,13 A One Health approach, which considers the interconnectedness of human, animal, and environmental health, is also important.12 Integrating data across African health systems14 and ensuring real-time information sharing will be vital to advance understanding of transmission patterns. The lessons learned from COVID-19 must be fully integrated into future planning to ensure that Africa is better prepared for subsequent outbreaks, with a focus on self-reliance and resilience.24 African leaders need to increase national funding for health care, prevention, research, and for health protection, including specifically for the mpox response.25 Assistance from global development partners to African governments should come in the form of investment, collaboration, and equitable partnership for sustainable development rather than knee-jerk, crisis-dependent aid.26 IA reports funding from the European Union under grant agreement no 101046314 and the UK National Institute for Health and Care Research (NIHR) under grant NF-SI-0616–10037. Challenges Solutions Inadequate domestic funding for the mpox response and the health system Current over-reliance on donor funding The commitment by heads of state in Africa to spend 15% of national budgets on health (as in the 2001 Abuja Declaration) should be implemented and is crucial for health and economic development Outbreak response infrastructure Subnational supporting infrastructure essential in every nation to support the progress on establishing some National Public Health Institutes and continental coordination by Africa CDC Invest in local and district level networks of disease surveillance and diagnostic and response infrastructure, including environmental and animal testing Technical skills and human resources Limited availability of skilled public health and laboratory staff at local centres, and insufficient industry expertise Invest in training and improve staff remuneration and working conditions Research and science Greater coordination and funding needed, building on regional and national centres of excellence in pandemic prone infections Build on Nursing & Allied Health Premium